Phytochemical Analysis and Antibacterial Potential of Papaya Leaf Extract (Carica papaya L.) against Salmonella typhi - Rusli, Rusli; Ratnah, St.; Ikbal, Ikbal; Vivi, Vivi; Asmawaty, Asmawaty; Rusdiaman, Rusdiaman (Media Kesehatan Politeknik Kesehatan Makassar, 2024)
Papaya plants are widely cultivated in various regions in Indonesia, including in Banrimanurung Village, West Bangkala District, Jeneponto Regency, South Sulawesi. Papaya Leaves (Carica papaya L.) are known to contain several secondary metabolites. Extraction was carried out by the macerani method using 96% ethanol solvent. Phytochemical screening is one way to determine the content of secondary metabolite compounds in plants. The purpose of this study was to determine the content of secondary metabolite compounds in Papaya Leaf extract (Carica papaya L.) grown in Jeneponto Regency. The results showed that Papaya Leaf (Carica papaya L.) tested positive for alkaloid, flavonoid, tannin, saponin, polyphenol, and steroid secondary metabolite compounds. Antibacterial activity was tested by disc diffusion method. The concentrations used were 2%b/v, 4%b/v, 8%b/v, positive control, and negative control. The average inhibition zone obtained from concentrations of 2%b/v, 4%b/v, 8%b/v, positive control, and negative control for Salmonella typhi is 8.67 mm, 9.00 mm, 10.00 mm, positive control 14.67 mm, while the negative control does not form an inhibition zone. Based on the results of the research conducted, it is concluded that Papaya Leaf extract (Carica papaya L.) has significant antibacterial activity against Salmonella typhi growth with the most optimal concentration being 8%b/v. Test the MIC and MKC values ​​using the liquid dilution method. The concentrations used were 0.25%; 0.5%; 0.75%; 1%; 1.25%; 1.5%; 1.75%; 2%; 4%; 6%; 8% b/v. The result of the study showed that the MIC (Minimum Inhibitory Concentration) of Papaya Leaf extract is found at a concentration of 1.75% b/v and the MKC (Minimum Killing Concentration) is found at a concentration of 6% b/v. This shows that Papaya Leaf extract (Carica papaya L.) effective to inhibit and kill Salmonella typhi bacteria. Keywords: Papaya Leaf, Extraction, Phytochemical Screening, Antibacterial, Salmonella typhi